Studies on Radon Concentration in Samples from Drinking Water at Hilla city, Iraq - Al-jnaby, Mohsin Kadhim Muttaleb (Al-Qadisiyah Journal of Pure Science, 2018)
This research measuring the radioactive gas radon in samples of drinking water in the city of Hilla, have been collecting 38 samples from different regions of Hilla in Babylon /central of Iraq has been the use a electronic detector of radon (RAD7) was calculated average radon concentration and the average of standard deviation and the highest concentration in A16 (0.193 ± 0.0211 ) Bq.L-1 and less concentration in A1 (0.0361± 0.00014) Bq.L-1 and the average of radon concentration (0.115 ± 0.048) Bq.L-1 and the annual effective dose was 0.413 mSv.y-1.